THE RELATIONSHIP BETWEEN THERAPEUTIC COMMUNICATION BY NURSES AND PATIENT SATISFACTION LEVELS IN THE INPATIENT WARD OF HOSPITAL X IN BATAM CITY - Napitupulu, Alex; Yunaspi, Didi; Badri, Isna Aglusi (Jurnal Keperawatan Sriwijaya, 2026)
Aim: The quality of hospital services is not only measured in terms of medical aspects, but also in terms of patient satisfaction. One important factor that influences satisfaction is therapeutic communication by nurses, as nurses are the health workers who interact with patients most frequently. The objective of this study was to determine the relationship between therapeutic communication by nurses and patient satisfaction levels in the inpatient ward of Hospital X. Method: This study is quantitative research, using an analytical design with a cross-sectional approach. The population in this study were people aged 18 years and above, with a required sample size of 85 people using purposive sampling. Data collection tools used questionnaires and data analysis in this study used the Spearman Rho test. Results: The results of this study showed that the p-value was 0.000 with a correlation coefficient of r = 0.457. This means that there is a moderate and significant relationship between therapeutic communication by nurses and patient satisfaction levels. Conclusion: The conclusion of this study is that there is a moderate and significant relationship between Therapeutic Communication by Nurses and Patient Satisfaction Levels in the Inpatient Ward of Hospital X in Batam City in 2025.